Spatial genetic diversity and populational differentiation of Ternstroemia sylvatica (Ericales: Pentaphylacaceae) in eastern Mexico - Hernán Alvarado-Sizzo; Isolda Luna-Vega; Edna Arévalo-Marín; Othón Alcántara-Ayala; Gerardo Rivas (PLoS ONE, 2025)
Ternstroemia sylvatica inhabits several temperate and tropical montane forests in eastern Mexico. Its current discontinuous distribution results from both natural and anthropogenic fragmentation. We assessed the genetic diversity and population differentiation of T. sylvatica across its distribution range using 18 microsatellite markers. We sampled 366 individuals from 16 populations, analyzing genetic diversity ( He ) and population structure via STRUCTURE and Discriminant Analysis of Principal Components (DAPC). Our results revealed high genetic differentiation ( F ST = 0.21), with most genetic variation occurring within populations (79.50%). STRUCTURE analysis identified two major genetic clusters: a northern group, comprising the populations with the lowest genetic diversity, and a southern group with higher genetic diversity ( He = 0.59–0.73) geographically structured into ten subgroups. Additionally, the results suggest historical fragmentation, limited gene flow among populations and inbreeding, as a heterozygote deficit is prevalent across populations. The high genetic diversity in specific populations indicates potential hybridization with other sympatric Ternstroemia species.